Blunted Heart Rate Circadian Rhythms in Small for Gestational Age Infants during the Early Neonatal Period - Begum, Esmot Ara; Bonno, Motoki; Sasaki, Naoya; Omori, Yusuke; Matsuda, Kazuyuki; Sugino, Noriko; Tanaka, Shigeki; Yamamoto, Hatsumi; Ido, Masaru (American Journal of Perinatology, 2012)
Infants born with intrauterine growth restriction are at increased risk for adverse cardiovascular outcomes in neonatal and later life. Although circadian rhythm is a prognostic marker of cardiovascular health, the concern over the circadian rhythm of these infants is rarely observed. To determine the influence of intrauterine growth retardation on the pattern of circadian rhythm, heart rate (HR) circadian rhythmicity was analyzed in 39 small for gestational age (SGA; birth weight and height below <−2.0 standard deviation score [SDS]) and 117 appropriate for gestational age (AGA; >−1.5 to <1.5 SDS) infants within 72 hours of birth using spectral analysis and cosinor analysis. Amplitude, midline estimating statistic of rhythm, and acrophase calculated from circadian rhythm were analyzed with clinical variables. A significant HR circadian rhythm was observed in 23.1% of the SGA and 24.8% of the AGA group without significant differences; however, SGA infants exhibited remarkable smaller amplitudes compared with AGA in all gestational age (GA) groups (p < 0.001). Amplitudes in AGA infants were positively correlated with the GA or body composition relevant variables (p < 0.001, respectively), but not SGA infants. The blunted HR circadian rhythmicity in SGA infants showed in this study might indicate the vulnerability to pathophysiological condition and could potentially refer to cardiovascular disease in later life.
Keywords: small for gestational age; appropriate for gestational age; neonate; amplitude; acrophase; intrauterine growth retardation